KODE ETIK - Nur Hasyim M Khafid; Raja Rahmat Rayhan; Dimas Alfian; Yahya Sugiarti (Kampus Akademik Publiser, 2024)
The code of ethics for the legal profession is an ethical guideline that must be adhered to by all legal scientists to maintain moral quality and professionalism. The code of ethics reflects the moral values ​​inherent in the profession and is prepared without external coercion. This code functions as social control, preventing interference from other parties, and avoiding internal conflict. Apart from that, a code of ethics is important to maintain the professionalism and clarity of duties of members of the legal profession, including advocates, notaries, judges, and others. Indonesia as a rule of law regulates a professional code of ethics in law, strengthening the role of free and responsible law enforcers. Enforcement of the code of ethics involves monitoring and providing sanctions for violations to maintain the reputation of the profession in the eyes of the public. Code of ethics and law enforcement are two different but interrelated aspects, where code of ethics enforcement focuses on implementing professional moral guidelines, while law enforcement includes broader legal norms to maintain order in society.